Nutritional characteristics of ancient Tuscan varieties of Triticum aestivum L. - Ghiselli, Lisetta; Rossi, Eleonora; Whittaker, Anne; Dinelli, Giovanni; Baglio, Adriano Pasqualino; Andrenelli, Luisa; Benedettelli, Stefano (Italian Journal of Agronomy, 2016)
Bread wheat (Triticum aestivum L.) is an important cereal in human consumption. In recent years, there has been a growing interest in ancient wheat varieties. The latter represent an important source of germplasm, characterised by a broader genetic base and, therefore, a potential source of biodiversity. The objective of the study was to ascertain the optimal balance between the presence of secondary metabolites having beneficial effects on health and technological features that ensure successful baking quality. The experimental trial was performed in 2011-2012 on three organic farms located in three different areas within the province of Siena (Tuscany). In each location, an overall evaluation of the commercial, rheological and functional properties of five ancient Tuscan bread wheat varieties (Andriolo, Frassineto, Gentil rosso, Inallettabile 96, Verna) as compared with a commercial modern variety (Palesio) was carried out. The ancient varieties were compared both singularly (pure) and in combination (mixtures) of two varieties in equal proportion, respectively. Biometric and productive parameters were detected for each plot (32 plots in each farm). Macro- and trace elements, polyphenols, flavonoids and antioxidant activity (antiradical power, ARP) were similarly determined on representative whole grain samples. Rheological analysis was carried out on flour samples. The multivariate statistical analysis using principal components analysis was performed on all variables analysed. The results showed a significant environment effect on the different parameters measured and did not reveal significant improvements in the variables measured when varieties were cultivated in mixtures. However, the study did reveal various interesting trends that are warranting of further investigation. The most interesting effect from a nutritional and functional point of view is the relationship between ARP, rheological properties, protein content and gluten content. These connections permit the potential towards the improvement of ancient varieties.